A study on factors related to intention to purchase organic foods among UTM postgraduate students / Nurul Nadhirah Abdul Aziz and Nur Hamira Mohamad Zam - Abdul Aziz, Nurul Nadhirah; Mohamad Zam, Nur Hamira (2022)
Most people forget how important it is to choose food, they may look at the price or the condition of the food without knowing the content or how it’s processed. They also probably think whatever food that the mall or the market sells is safe. So, organic food is considered as the food that is not made by extra ingredients, chemical additives nor processed by radiation exposure (Hossain & Pei, 2016). Due to all the reasons why conventional food is not a good choice to eat or buy, organic food has become a top choice for people. They are starting to acknowledge food safety and this has made increasing numbers on the organic food market by people’s demand for healthier diets, particularly organic foods (Saleki, Quoquab, & Mohammad, 2019). People believed that this type of food is beneficial to human health rather than having negative consequences on them and this was caused by high societal interest (Yean, Iris, & Lee, 2019; Huber, Rembiałkowska, Średnicka, Bügel, & van de Vijver, 2011). There are several factors that lead to people purchasing organic food. For this study, the researchers intended to know what makes the postgraduate students of Department of Bioscience in the Faculty of Science from Universiti Teknologi Malaysia choose to buy organic foods. This study examines the concept of the influence of the students' intention in purchasing organic foods. The conceptual framework proposes a direct relationship between the determinants of environmental concern, health factors with food safety, knowledge of health factors and perceived value of health towards students buying behaviour for Postgraduate Student in UTM Skudai. In this study, the population of UTM Skudai postgraduate students from Department of Bioscience, Faculty of Science is 195 and the sample size was all respondents in the population.